Pengaruh Pendapatan Asli Daerah (Pad) Terhadap Belanja Modal Pemerintah Darah Kota Sukabumi - Utary, Vinny Siti (Jurnal Akuntansi UMMI, 2021)
The research aims to know the influence of the income wether the Local Own Revenue (PAD) and the Special Allocation Fund (DAK) have a positive effect towards On Capital Expenditure Regional Government of Sukabumi City. The method used in this research is assosiatif and descriptive method. Data collection techniques in this research is secondary data, and the methods used are documentation. The sample in this study is the Budget Realization Report (LRA) Regional Government of Sukabumi City from 2016-2018 using 36 samples of data, research tools used were multiple linier regression. The result of this aims can be concluded that the Local Own Revenue (PAD) have a positive and significant impact On Capital Expenditure Regional Government of Sukabumi City.